STRATEGI KESANTUNAN BERBAHASA DALAM KRITIK PENONTON TERHADAP FILM MERAH PUTIH: ONE FOR ALL DI PLATFORM TIKTOK - Wasi Alya Rizki; Didin Sahidin; Cecep Dudung Julianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the forms of positive and negative criticism and analyze the politeness strategies used by the audience in responding to the film